DOSE COMPARISON AND SIDE EFFECT PROFILE OF METFORMIN EXTENDED RELEASE VERSUS METFORMIN IMMEDIATE RELEASE - Hameed, Maliha; Khan, Khurshid; Salman, Sadia; Mehmood, Nasir (Journal of Ayub Medical College Abbottabad, 2017)
Background: Diabetes Mellitus type 2 is very common worldwide, with majority of cases in Asia Pacific region. Metformin is the first line therapy, along with lifestyle modification for all type 2 diabetics as recommended by ADA. Metformin is available as conventional Metformin Immediate Release (MIR) and Metformin Extended Release (MXR). Metformin XR has better gastrointestinal tolerability and fewer side effects as compared to Metformin IR, with similar efficacy regarding anti-hyperglycaemic effects. The objective of this study was to determine whether metformin XR is as effective as Metformin IR in maintaining glycaemic control at equivalent doses or even at reduced doses; and to compare the side effect profile of the two preparations. Methods: This randomized control trial was conducted at Medical and Endocrinology OPD of Jinnah Hospital Lahore A total of 90 type 2 diabetics of both genders were recruited using nonprobability purposive sampling. Patients were randomized into 3 groups; 30 in each group. Group 1 received Metformin IR 1000 mg twice daily; group 2 received metformin XR 1000mg twice daily; and group 3 received metformin XR 500 mg twice daily, for a period of three months. HbA1c was done at baseline and after three months of therapy along with fasting blood sugars and random blood sugars weekly. Results: The mean age of patients was 46±9 years, with 54% being males and 46% being females. There was a 1% reduction in HbA1c in group 1, 0.7% reduction in group 2 and only 0.4% reduction in group 3. Similarly, all three therapies were equally effective in reducing blood sugar fasting and blood sugar random at three months. Side effects namely diarrhoea, dyspepsia and flatulence were greatest with Metformin IR (40%) but less than half with Metformin XR at equivalent dose and negligible at half the dose. Conclusions: All three Metformin groups were effective in reduction of HbA1C and glycaemic control clinically and there is no statistical difference in HbA1c reduction among groups at three months. Keywords: Diabetes Mellitus type 2, Metformin, Immediate release; Metformin extended release, Efficacy; Side effects